Work-in-progress: advanced ahead-of-time compilation for javascript engine - Park, Hyukwoo; Sungkook Kim; Soo-Mook Moon (CASES : 2017 International Conference on Compilers, Architectures and Synthesis for Embedded Systems : 15-20 October 2017, 2017)
JavaScript is heavily used in the web, yet it is much slower than other languages. To improve the JavaScript performance, ahead-of-time compilation (AOTC) has been used, either to reuse the bytecode or the machine code generated by the baseline just-in-time compilation (JITC). JavaScript engines today employ high-performance optimizing JITC. So, we propose an AOTC that reuses the code generated by the optimizing JITC. It is more challenging than existing AOTCs since we need to handle more complex address relocation issues. Our preliminary evaluation shows that the proposed AOTC is promising, though.